Converging SPI_S Designs: An Evaluation of Configurable IP Development - Lundgren,Sakarias; Modica,Benjamin (2025)
This thesis explores the configurability of IPs for ASICs by looking into the design of SPI_S, an IP used for communication between ASICs and peripheral devices. Configurability is explored to reduce manual labor when requirements set on the IP change between projects. The thesis looks into the challenges of developing a configurable IP, including architecture, design, and verification. In addition, how configurability affects performance, area, and power consumption. The results show that SPI_S can be made more configurable and still meet requirements set on performance. However, area and power consumption tend to increase, though tying configuration ports to fixed values enables synthesis optimizations that can significantly reduce this overhead when static configurations are used. Configurability also comes with challenges throughout the development cycle. During development, a comprehensive UVM testbench developed alongside the design is of utmost importance, to ensure that implemented features are properly validated in all the different configurations.
Keywords: Configurable IP; IP development